Phenotypic recurrent selection on herb growth yield of citronella grass (Cymbopogon nardus) grown in Egypt - MOHAMED M. IBRAHIM; KHALID A. KHALID (Nusantara Bioscience, 2013)
Abstract. Ibrahim MM, Khalid KA. 2013. Phenotypic recurrent selection on herb growth yield of citronella grass (Cymbopogon nardus) grown in Egypt. Nusantara Bioscience 5: 70-74. This investigation was conducted in four generations: base population (G0, G1, G2) and G3 (clone selection generation) to evaluate the genetic variability of citronella clones. Thirteen clones were selected from base population to study the herb growth yield characters and oil production as well as genetic parameters, correlation, and regression. Results were recorded for herb growth characters (i.e. plant high (PH), no. of tillers (NOT), dry yield (DY), viability percentage (VP) and oil production. Significant variation was observed among citronella clones in base population for most studied traits. Wide range of mean values was observed among the characters for generations and cuts in most traits. High heritability values (0.95, 0.93, 0.89 and 0.72) were estimated in NOT, LG, HY and VP., respectively. Clone code no. 39/3, 17/4 and 8/1 gave highest values of dry weight, oil yield, and viability percentage. Selected clones showed significant positive regression and correlation between dry weight and each of number of tillers and linear growth. On the contrary, viability percentage had significant negative correlation and regression with other characters. These results raveled high yielding selected citronella clones will be utilized in medicinal plant breeding program.